Yervandashat – Yervandakert. The Yervandid/Orontid capital and its Urartian past - Muradyan , Syuzanna (ARAMAZD: Armenian Journal of Near Eastern Studies, 2025)
The study of the palace, a monumental structure in the area of the Yervandakert archaeological complex, opened a new page in the formation of the Hellenistic cities of Ancient Armenia, filling the gap of cultural interdependence in those cities after the collapse of the previous statehood, the Urartian kingdom. With the excavations of the latter, traces of the interconnection of old and new cultures, the re-operation of the palace with Urartian foundations were brought up, including the addition of the ‘susi’ tower-shaped structure adjacent to the palace, one of the unique manifestations of Urartu, which was connected with the transfer of architectural traditions from Armavir to Yervandakert by Yervand the Last, king of Armenia. The excavations of Yervandakert paradise once again confirm that after the fall of the Urartian kingdom, the Urartian heritage finds its various manifestations in the culture of Yervandid Armenia.